'They shouldn't be coming to the ED, should they?' A qualitative study of why patients with palliative care needs present to the emergency department. Issue 4 (12th May 2016) - Green, Emilie; Shaw, Sara E; Harris, Tim
Abstract : Introduction: Across the developed world, there are concerns about 'inappropriate' use of the emergency department (ED). Patients with palliative care needs frequently attend the ED. Previous studies define the 'reason' for presentation as the 'presenting symptom', which ignores the perspectives of service users. This paper addresses an acknowledged gap in the literature, which fails to examine the decision-making process that brings patients to the ED. Methods: In-depth narrative interviews were conducted with 7 patients (known to a specialist palliative care service and presenting to the ED during a 10-week period) and 2 informal caregivers. Analysis drew on 'Burden of Treatment Theory' to examine the meaning attributed by participants to their experience of serious acute illness, their capacity for action and the work required to access emergency care. Results: 5 themes were identified about how and why emergency services were accessed: capacity for action, making sense of local services, making decisions to access emergency services, experience of emergency care and coping with change. All narratives captured concerns surrounding the complexity of services. Participants struggled to piece together the jigsaw of services, and were subsequently more likely to attend the ED. Differences between the ways that patients with chronic obstructive pulmonary disease and cancer accessed the ED were prominent. Conclusions: Further work is needed to understand and respond to decisions leading patients with palliative care needs to the ED, particularly in the context of locally fragmented services, poor signposting and confusion about available healthcare. The perspectives of service users are essential in shaping emergency care.